Feeding melengesterol acetate (MGA) in advance of estrus synchronization of virgin beef heifers - B.T. Gray; T.T. Marston (Kansas Agricultural Experiment Station Research Reports, 2005)
The objective of this experiment was to determine if a 7-day feeding of melengesterol acetate (MGA) about 2 months before the breeding season would have an effect on puberty onset, response to estrous synchronization, and fertility. "Progesterone priming" with MGA increased the number of heifers that began cycling before estrous synchronization. This did not increase the percentage of heifers that were observed in standing heat after estrous synchronization, however, regardless of whether standard MGA/PGF or Select Synch protocol was used. The conception rates and overall pregnancy rates were similar between treatments. Many factors affect the reproductive performance of replacement heifers; slight decreases in the age of puberty onset seem to have little effect.
Keywords: Cattlemen& #x27; s Day; 2005; Kansas Agricultural Experiment Station contribution; no. 05-144-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 943; Beef; Melengesterol acetate (MGA); Estrus synchronization; Virgin beef heifers